ANALISIS ELEMEN-ELEMEN BRAND EQUITY TOKO SWALAYAN DI MAGELANG - Kurnia, Marlina Kurnia; Nurbudi, Bambang Nurbudi (Universitas Muhammadiyah Magelang, 2005)
This research attems to identity and analyze elemen-elemen of brand equity that cover brand awarness, brand association, perceived quality and brand loyalty Armada Swalayan. Procedure judgment sampling used to explore for 100 responden and than analized by descrpting trough grafik, tabulation, mean and standart deviation. Specifically for brand association used realibelity test spearman-brown method and cohran test for the research instrumen. The result from this research, Brand Awareness : responden conscious about Swalayan in Magelang on behalf to make dicition buying was in top level. This shown with 60% responden in top of mind and 1% in unaware level. Brand association of rentabilitase experiment are r11 > r product moment, so instrumen will be used for the experimental is uptodate. Doing tes cohran until test step VII have the statistik Q < X2 and than give result is asosiasi from Swalayan in Magelang should very near to the consument are, condusive, advantage and confortable; cheapest; clean and large. Swalayan in Magelang association is wonderful shop center, full fasility, full comodity with high quality are association can't be connected with the brand. Brand Perceived Quality : all responden result with performance Swalayan in Magelang disincrease than importance result. Its swowing that performance quality brand Swalayan in Magelang not yet to standart with standart performance quality responden whises. Brand Loyalty : Equals respondent in the switcher steped on the biggest part is 81%. And than brand loyalty in the one step disincrease prosentase of respondent more than smallest, are habitual buyer 41%, satisfied buyer 34%, liking the brand 35% and committed buyer 54%. Although presentase at the committed buyer level is high. But recorder to standart deviation, one of tolerant with standarrt deviation can be transferred responden committed buyer Swalayan in the dis-agree posision.